2016
DOI: 10.1007/s10578-016-0659-y
|View full text |Cite
|
Sign up to set email alerts
|

Agreement Between Parent- and Self-Reports of Psychopathic Traits and Externalizing Behaviors in a Clinical Sample

Abstract: A number of studies have identified discrepancies in informant ratings of externalizing behaviors in youth, but it is unclear whether similar discrepancies exist between informants when rating psychopathic traits. In this study, we examined parent-child agreement on ratings of both psychopathic traits and externalizing behaviors, and examined the factors that influence agreement in both of these domains. A total of 282 children between 7 and 16 years (M = 10.60 years, SD = 1.91) from an outpatient child psychi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…It is noteworthy that several studies have found poor parent-child agreement in the assessment of internalizing [41,42] and externalizing symptoms [43] in children. The present study relied on the information from the parents to determine children's ADHD and ODD symptoms, which may influence the parent-children agreement on the CU traits.…”
Section: Factors Related To Adolescent-parent Disagreement On Cu Traitsmentioning
confidence: 98%
“…It is noteworthy that several studies have found poor parent-child agreement in the assessment of internalizing [41,42] and externalizing symptoms [43] in children. The present study relied on the information from the parents to determine children's ADHD and ODD symptoms, which may influence the parent-children agreement on the CU traits.…”
Section: Factors Related To Adolescent-parent Disagreement On Cu Traitsmentioning
confidence: 98%
“…Such evidence would not only suggest that the three CPTI dimensions are at least in part dependent on each other in their relation to the external criterion measures but also would corroborate with the commonly accepted view that psychopathic personality can best be described as a constellation of co-occurring traits (e.g., Colins, Fanti, Larsson, et al, 2017). Finally, informant agreement in the area of youth psychopathy is typically studied while relying on child self- and parent-reports (e.g., Ooi et al, 2017) or on mother and father reports (e.g., Fanti, Kyranides, Lordos, Colins, & Andershed, 2018). Actually, relatively few studies examined how well parents and teachers correspond when rating a child in terms of psychopathic traits.…”
Section: This Studymentioning
confidence: 99%